Morphological notes on the worker and queen larvae of the thief ant solenopsis helena (Hymenoptera, Formicidae, Myrmicinae) from Brazil - Paterson Fox, Eduardo Gonalves; Solis, Daniel Russ [UNESP]; Rossi, Monica Lanzoni; MacKay, William; Pacheco, Jose (De Gruyter, 2011)
Young and mature larvae of queen and workers of the thief ant, Solenopsis helena, are herein described for the first time. Specimens were treated and described by usual methods of light and scanning electron microscopy. Many of the observed characteristics confirmed traits of the thief ant larva, reinforcing the assumption that they are a distinct group from fire ants. The larva of S. helena can be recognized from other close species by details of the mouthparts, but seem extensively similar to Solenopsis molesta. These findings are useful for taxonomic studies and phylogenetic inferences.
Keywords: ant morphology; Larval description; scanning electron microscopy; Solenopsidini; taxonomy